Analysis of Treatment Adherence and Association with Blood Pressure Control Among Outpatients with Hypertension in Vietnam - Cuba Friendship Hospital - Phuong Nga, Pham Thi; Thi Mai Phuong, Nguyen; Duc Chinh, Cao; Thi Hai, Ngo; Thi Thuy Hang, Le; Thanh Hai, Nguyen; Thi Thu Trang, Tran (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2026)
A cross-sectional descriptive study combined with retrospective data was conducted on 385 patients diagnosed with hypertension and treated as outpatients at Viet Nam–Cuba Friendship Hospital from December 1 to December 31, 2024. Eligible patients had a hypertension diagnosis for at least six months. Data were collected at six time points, including the study time point (T6) and five previous outpatient visits (T1–T5), corresponding to July through November 2024. The mean age of the patients was 70.4 ± 7.3 years; most were aged ≥65 years, and women accounted for 72.5%. The majority of patients had a hypertension duration of three years or longer (88.3%) and at least one cardiovascular risk factor (98.4%). Approximately 80% of patients adhered to scheduled follow-up visits. Good medication refill adherence, assessed by the proportion of days covered (PDC) during T1–T6, was observed in 70.1% of patients. According to the MARS-5 scale, the medication adherence rate was 79.7%, with a mean score of 24.3 ± 1.5 (min-max: 16–25). The proportion of patients achieving target blood pressure at T6 was 26.2%. In multivariate logistic regression analysis among patients who had not achieved target blood pressure at T5, those with good medication adherence were significantly more likely to achieve target blood pressure at T6 compared with non-adherent patients (adjusted OR [95% CI]: 9.01 [1.71–47.60], p = 0.010). Good treatment adherence significantly increased the likelihood of achieving target blood pressure in the subsequent period among patients who had not yet reached target blood pressure.